English - Language Academic Writing in the Context of Academic Mobility: Array - Kriukova, Olha (Journal of Danubian Studies and Research, 2020)
The article deals with the role and aspects of studying English-language academic writing in the context of academic mobility. The international cooperation in higher education in the Lower Danube Euroregion is detailed on the basis of Izmail State University of Humanities. Various methodological approaches to teaching academic writing in higher education are analyzed. The study shows that applying an integrated approach is most effective for building an academic writing competency.